Height gain in Ullrich-Turner syndrome after early and late growth hormone treatment start: results from a large retrospective German study and potential basis for an individualized treatment approach - Bettendorf, Markus; Inta, Ioana; Doerr, Helmuth G.; Hauffa, Berthold P.; Mehls, Otto; Ranke, Michael B. (Hormone research in paediatrics, 2020)
Background: Ullrich-Turner syndrome (UTS) girls often present with short stature in adolescence to the endocrinologist when the efficacy of growth hormone (GH) to improve growth remains unknown and parameters to estimate individual GH responsiveness have yet to be determined. Objective: Retrospective evaluation of adult height (AH) and predicted adult height at GH start (descriptive model of Ranke, Model PredAH) in early and late GH-treated German UTS patients. Subjects/Methods: 313 patients treated with GH, early [chronological age (CA) at GH start <12 years, n = 259] or late (CA at GH start ≥12 years, n = 54) who reached AH were selected from KIGS (Pfizer International Growth Database). Results: AH (152.5 ± 5.9 vs. 151.1 ± 5.4 cm, p = n.s.) after GH treatment for 7.5 ± 2.12 years (GH start early) and for 5.2 ± 1.2 years (GH start late) were similar (p = n.s.) as Model PredAH (155.7 ± 4.8 vs. 154.7 ± 4.8 cm; p = n.s.) but higher (p < 0.001) than projected adult height (Ranke, ProjAH; 148.2 ± 5.5 vs. 145.2 ± 6.7 cm; p = 0.001). Total height gain over ProjAH was 4.3 ± 4.6 cm (GH start early) and 5.8 ± 4.7 cm (GH start late, p = 0.021), respectively. Conclusions: GH may improve AH in UTS patients even when started late. The individual growth response could be estimated by the descriptive Model PredAH independent of age at treatment start.
Gesehen am 24.11.2020